A simple model of the financial crisis of 2007-9 with implications for the design of a stimulus package - Kaushik Basu (Cornell University, Center for Analytical Economics (CAE), 2009)
The financial crisis of 2007-09 began as a local problem in the mortgage finance market in the United States and Europe but, within months, escalated into a general global financial crisis, resulting in collapsing investment not just in developed nations but also in Shanghai, Rio and Mumbai, and has led to a general recession worldwide. The paper builds a rational-expectations, microeconomic model of why the local crisis escalated into a general freeze in credit flows. It then isolates two very different kinds of interventions needed to restore the economy back to health, arguing that government stimulus policy has not had enough impact because a failure to understand the need for the dual intervention.
Keywords: 330; financial crisis; recession; multiple equilibria; credit markets; credit ratings; Finanzmarktkrise; Ansteckungseffekt; Internationaler Finanzmarkt; Wirtschaftsmodell; Welt